ASSESSMENT IN LITERACY IN EARLY CHILDHOOD: THE ROLE OF PARENTS IN THE OBIO-AKPOR LOCAL GOVERNMENT AREA IN NIGERIA - UzosikeNgozi, Chima (PEOPLE: International Journal of Social Sciences, 2018)
This study sought to find out the roles parents play in assessment in literacy of their children in the Obio-Akpor Local Government Area in Nigeria. The design that was used for the study was the descriptive survey. Using the simple random sampling procedure, 12public pre-schools in the Universal Basic Education in Obio-Akpor Local Government Areawere selected for study. Data gathered from parents and teachers with using questionnaire, analysed using the descriptive statistics namely frequencies and percentages. The major findings were that, having reading sessions with children at home; engaging in shared reading with children and providing varieties of reading materials to children were some of the roles parents played in assessment in literacy of their children. Again, development of vocabulary and print awareness; and development of reading comprehension and decoding abilities were the major impact of parental involvement in assessment in literacy in early childhood. The study recommended that, parents should engage in reading activities such as reading aloud to children at home and share reading with their children at home to enhance their literacy development. Again, parents and teachers should develop positive and mutual communication and support to help assess the literacy development of children both in school and at home.